Atenção ao idoso da comunidade: um olhar sobre a fragilidade em equipes de saúde da família - Alexandrin, João Victor Rodrigues (Universidade Federal de São Carlos, 2021)
INTRODUCTION: It is extremely important that community health workers have a broad understanding of aging and the elderly. Therefore, the aggregation of knowledge related to aging and the adherence to actions in this area are of great importance for training, professional qualification and continuing education, which enables a greater bond with the elderly. OBJECTIVE: To evaluate knowledge about old age and to analyze the contribution of audiovisual material about old age, frailty and care for the elderly in a city in the interior of São Paulo. METHOD: This is an exploratory study with a quantitative approach. Seven members of the health teams from the Family Health Units participated in the study, of both sexes, under the attention of the Family Health Center (NASF) in the city of São Carlos. They were evaluated using the Palmore-Neri-Cachione instrument (Cachione, 2002) that assesses the knowledge of professionals about aging and the elderly and 3 videos were presented on specific themes of aging and the elderly, elaborated for this study by the self. The data in this study were coded and organized in a Microsoft Excel database. Descriptive statistics were used, as measures of central tendency (simple frequency, average, median, minimum and maximum). RESULTS: The average number of correct answers was 10.2%, with a scale of less than or equal to 11 being described as having little or less gerontological knowledge. The results presented in the satisfaction survey, indicate that the videos made a lot of contribution regarding the topics covered. The average satisfaction was 6.6 points. FINAL CONSIDERATIONS: lack of adequate qualification on the themes explored. In addition, the construction of audiovisual material on topics related to frailty in the elderly, stereotypes about old age and long-term care has made contributions so that professionals have greater contact with the subject and, consequently, more knowledge
Care for the older people in the community: a look at the frailty in family health teams
Keywords: Profissionais da Saúde; Idoso; Educação permanente; Atenção Primária à saúde; Old people; Permanent education; Primary health care; OUTROS